Two-group bubble size distribution evolution in vertical two-phase flow: Mechanistic model development and evaluation in a tight-lattice rod bundle - Xiao Yao; Zhang Hengwei; Yan Xu; Gu Hanyang (National Science Open)
Two-phase flow with complex phase interfaces is commonly observed in both nature and industrial processes. The bubble size distribution (BSD) is a crucial parameter in gas-liquid two-phase flow, impacting various flow characteristics including interfacial forces, void fraction distribution, and interfacial area transport. Throughout the flow progression, the BSD changes along the channel due to variations in pressure and interactions among bubbles. Accurately predicting the evolution of BSD can enhance the modeling of two-phase flow. This study presents a novel BSD evolution (BSDE) model, where the governing equation for the probability density function is formulated by considering the conservation of bubbles within a one-dimensional control volume in the channel. The downstream BSD is predicted based on the upstream BSD and the effects of pressure variations and bubble interactions along the channel. To account for the multiscale nature of the two-phase flow, the bubbles are categorized into small groups (G1) and large groups (G2). Six distinct source term distributions for intra/inter bubble interactions have been developed. Each source term accounts for the distributions of consumed and generated bubbles, ensuring the conservation of bubble volume through constraints on model coefficients. The model has been tested on a tight-lattice rod bundle using experimental data, with deviations of less than 5% and 15% for G1 and G2 flow, respectively. Since the model development is independent of specific geometry, the framework of the BSDE model can also be effectively applied to channels of varying shapes.